Gaetano Mosca And The Rulling Class Analysis of Elite Group Domination in the Government System in Indonesia - Hamat, Yulianus Evantus; Pandor, Pius; Darus, Yulius; Nasar, Yulianus Lihong (Malikussaleh Social and Political Reviews, 2024)
The main focus of this article is to analyze the role and dominance of elites in the government system in Indonesia in the light of Gaetano Mosca's concept of the "ruling class". The current government situation in Indonesia is dominated by elite groups. The role of elites in determining policy is very dominant. Various policies and decisions are determined by elites who have important status and roles in the government arena. This phenomenon has an impact on the reality of people who do not have a role in government.   Thus, it is the elite who dominate or have power. This is exactly what Gaetano Mosca, an Italian-born sociologist and philosopher who pays attention to politics, calls for. In order to overcome problems arising from the domination of elite groups, there needs to be a reform mechanism. The mechanism is carried out through democratic processes such as elections or through social and political pressure from the masses. Effective reform can bring in more competent individuals into the ruling class, while overthrow can stop the cycle of oppression that is detrimental to the state. The aim of this research is to analyze the role of elites in government in Indonesia, and to see how elites maintain and utilize their power. The method used is literature study using Gaetano Mosca's The Ruling Class as a primary source. This research finds that the dominance of political elites in Indonesia plays a central role in policy formation and determining decisions taken in the government system.